2011
DOI: 10.1017/s0022112010004726
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic/transcendental disturbance growth behind a row of roughness elements

Abstract: This paper is a continuation of the work begun in Goldstein et al. (J. Fluid Mech., vol. 644, 2010, p. 123), who constructed an asymptotic high-Reynolds-number solution for the flow over a spanwise periodic array of relatively small roughness elements with (spanwise) separation and plan form dimensions of the order of the local boundary-layer thickness. While that paper concentrated on the linear problem, here the focus is on the case where the flow is nonlinear in the immediate vicinity of the roughness with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The resulting flow is formally nonlinear in the intermediate wake region, where the streamwise distance is large compared to the roughness dimensions but small compared to the downstream distance from the leading edge, as well as in the far wake region where the streamwise length scale is of the order of the downstream distance from the leading edge. In contrast, the flow perturbations in both of these wake regions were strictly linear in the earlier work by Goldstein et al (2010Goldstein et al ( , 2011. This is an important difference because the nonlinear wake flow in the present case provides an appropriate basic state for studying the secondary instability and eventual breakdown into turbulence.…”
mentioning
confidence: 64%
“…The resulting flow is formally nonlinear in the intermediate wake region, where the streamwise distance is large compared to the roughness dimensions but small compared to the downstream distance from the leading edge, as well as in the far wake region where the streamwise length scale is of the order of the downstream distance from the leading edge. In contrast, the flow perturbations in both of these wake regions were strictly linear in the earlier work by Goldstein et al (2010Goldstein et al ( , 2011. This is an important difference because the nonlinear wake flow in the present case provides an appropriate basic state for studying the secondary instability and eventual breakdown into turbulence.…”
mentioning
confidence: 64%
“…Since the equations are nonlinear, the convergence was achieved by a relaxation method; this was done by including time derivate terms in the equations that were converged to zero, using an appropriate preconditioning technique applied to the continuity equation. The linearized boundary region equations (13)(14)(15)(16) were solved using a similar scheme as described in GSDC.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…It was shown that the flow in the proximity of the roughness elements decays algebraically over a very short streamwise distance behind the roughness elements, and then breaks down in the downstream region. In a following article, Goldstein et al 16 extended the analysis to second order and showed that the downstream wakes exhibit algebraic/transcendental growth and that the location of growth onset moves closer to the roughness elements with increasing roughness height.…”
Section: Introductionmentioning
confidence: 99%
“…The primary effects of surface imperfections can be characterized by their impact on receptivity and linear amplification when the transition occurs via receptivity and linear growth followed by a sequence of nonlinear effects (Goldstein et al 11 ). The surface imperfections may introduce substantial changes in the boundary layer instability mechanisms, such as the onset of unsteady vortex shedding in a low-speed boundary layer (Acarlar and Smith; 1 Klebanoff et al, 20 Goldstein et al 11,12 ). Prior experimental measurements (e.g., White et al, 34,35 Reshotko 24 ) showed that surface imperfections have the potential to accelerate or delay the transition to turbulence, depending on the shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…Two step configurations of forward and backward facing types, and three 'streak strengths' (quantified by the difference between the maximum and minimum of the high-and low-speed regions, respectively) are considered. We numerically solve the boundary region equations subject to upstream boundary conditions as derived in Goldstein et al 11,12 The generalized Rayleigh pressure equation is solved as an eigenvalue problem to determine the growth rates associated with the secondary instabilities. It is found that as the height of the step is increased beyond 0.5 of boundary layer displacement thickness, the growth rate reduces at the peak streamwise wavenumber of the instability.…”
mentioning
confidence: 99%